Pseudorabies virus uses clathrin mediated endocytosis to enter PK15 swine cell line - Andreu, Sabina; Agúndez, Carmen; Ripa, Inés; López-Guerrero, José Antonio; Bello-Morales, Raquel (Frontiers in Microbiology, 2024)
Pseudorabies virus (PRV), a herpesvirus responsible for Aujeszky's disease, causes high mortality in swine populations. To develop effective and novel antiviral strategies, it is essential to understand the mechanism of entry used by PRV to infect its host. Viruses have different ways of entering host cells.Among others, they can use endocytosis, a fundamental cellular process by which substances from the external environment are internalized into the cell. This process is classified into clathrin-mediated endocytosis (CME) and clathrin-independent endocytosis (CIE), depending on the role of clathrin.Although the involvement of cholesterol-rich lipid rafts in the entry of PRV has already been described, the importance of other endocytic pathways involving clathrin remains unexplored to date. Here, we characterize the role of CME in PRV entry into the PK15 swine cell line. By using CME inhibitory drugs, we report a decrease in PRV infection when the CME pathway is blocked. We also perform the shRNA knockdown of the µ-subunit of the adaptor protein AP-2 (AP2M1), which plays an important role in the maturation of clathrin-coated vesicles, and the infection is greatly reduced when this subunit is knocked down. Furthermore, transmission electron microscopy images report PRV virions inside clathrin-coated vesicles. Overall, this study suggests for the first time that CME is a mechanism used by PRV to enter PK15 cells and provides valuable insights into its possible routes of entry.